Experimental Evaluation and Validation of Random Pulse Position Pulse Width Modulation for Industrial Drives - P. Arulkumar; N. P. Subramaniam (International Journal of Applied Power Engineering (IJAPE), 2015)
In industrial drives, random pulse width modulation (RPWM) is triumph for transferring of harmonic power from the detached spectrum of the output voltage to the unremitting spectrum, and offers the merits viz. The operation is free from an unpleasant acoustic noise and a mechanical vibration. The main objective of this paper is providing a comprehensive investigation of performance of random pulse position pulse width modulation (RPPPWM) for a three-phase voltage source inverter (VSI) fed induction motor drives. RPPWM scheme randomly varies the pulse position in every switching cycle, where the idea is inducing the random characteristics in the PWM pulses at fixed switching frequency. The competence in spreading the harmonic power of sinusoidal PWM (SPWM), random carrier PWM (RCPWM) and the RPPWM are compared using simulation. The results are corroborated through the prototype VSI designed. The developed RPPPWM based on a SPARTAN-6 FPGA (XC6SLX45) device, disperses the acoustic switching noise spectra of an induction motor drive